Intelligence in young adulthood and alcohol use disorders in a prospective cohort study of Danish men: the role of psychiatric disorders and parental psychiatric history - Just-Østergaard, Emilie (BMJ Open, 2019)
OBJECTIVES: The aims were to estimate the association between intelligence measured in young adulthood and risk of alcohol use disorders (AUD) in men and to investigate the potential modification of this association by psychiatric disorders, parental AUD and parental psychiatric disorders. DESIGN: Prospective cohort study based on a linkage of intelligence test scores from draft board examinations and register data on AUD diagnoses during 36 years of follow-up. SETTING: Denmark. PARTICIPANTS: 3287 Danish men from the Copenhagen Perinatal Cohort (born 1959–1961) who appeared before the draft board at a mean age of 18.7 years. PRIMARY OUTCOME MEASURE: First registration with AUD during follow-up was the primary outcome. Information on AUD was based on diagnoses retrieved from national hospital and outpatient treatment registers, defined according to the International Classification of Diseases. RESULTS: 361 (11.0%) men were registered with AUD during follow-up. Low intelligence scores were associated with increased odds of AUD adjusting for parental AUD, parental psychiatric disorders, maternal smoking during pregnancy, birth weight, maternal age at birth, parity and childhood socioeconomic position (OR per SD decrease in intelligence=1.69, 95% CI 1.49 to 1.92). Separate analyses indicated significant interaction (p<0.001) between intelligence and psychiatric disorders. The adjusted OR per SD decrease in intelligence score was 2.04 (95% CI 1.67 to 2.49) in men without other psychiatric disorders whereas the OR was 1.21 (95% CI 1.01 to 1.46) in men with other psychiatric disorders. No interaction was found between intelligence and parental AUD or between intelligence and parental psychiatric disorders. CONCLUSIONS: The association between intelligence in young adulthood and AUD is modified by other psychiatric disorders as low intelligence is primarily a risk factor for men without other psychiatric disorders. Future studies should take other psychiatric disorders into account when investigating associations between intelligence and AUD.